Polarization-Dependent Second Harmonic Diffraction from Resonant GaAs Metasurfaces - Loechner, Franz J. F.; Fedotova, Anna N.; Liu, Sheng; Keeler, Gordon A.; Peake, Gregory M.; Saravi, Sina; Shcherbakov, Maxim R.; Burger, Sven; Fedyanin, Andrey A.; Brener, Igal; Pertsch, Thomas; Setzpfandt, Frank; et al. (ACS Photonics, 2018)
Resonant semiconductor metasurfaces are an emerging versatile platform for nonlinear photonics. In this work, we investigate second-harmonic generation from metasurfaces consisting of two-dimensional square arrays of gallium arsenide nanocylinders as a function of the polarization of the fundamental wave. To this end, we perform nonlinear second harmonic microscopy, where the pump wavelength is tuned to the resonances of the metasurfaces. Furthermore, imaging the generated nonlinear signal in Fourier space allows us to analyze the spatial properties of the generated second harmonic. Our experiments reveal that the second harmonic is predominantly emitted into the first diffraction orders of the periodic arrangements, and that its intensity varies with the polarization angle of the fundamental wave. While this can be expected from the structure of the GaAs nonlinear tensor, the characteristics of this variation itself are found to depend on the pump wavelength. Interestingly, we show that the metasurface can reverse the polarization dependence of the second harmonic with respect to an unstructured GaAs wafer. These general observations are confirmed by numerical simulations using a simplified model for the metasurface. Our results provide valuable input for the development of metasurface-based classical and quantum light sources based on parametric processes.
CRIS-Team Scopus Importer:2023-04-20
Keywords: all-dielectric nanophotonics; Mie-resonances; nanophotonics; nonlinear Fourier imaging; nonlinear metasurfaces; second-harmonic generation